Γ‐sarcoglycan and dystrophin mutation spectrum in an Algerian cohort. Issue 1 (10th February 2017) - Dalichaouche, Imene; Sifi, Yamina; Roudaut, Carinne; Sifi, Karima; Hamri, Abdelmadjid; Rouabah, Leila; Abadi, Noureddine; Richard, Isabelle
ABSTRACT: Introduction: We report the genetic analysis of a large series of 76 Algerian patients from 65 unrelated families who presented with early onset severe muscular dystrophy and a clinical phenotype resembling limb‐girdle muscular dystrophy type 2C. Methods: To define the genetic basis of the diseases in these families, we undertook a series of analyses of the γ‐sarcoglycan ( SGCG ) and DMD genes. Results: Fifteen families were shown to carry SGCG variants. Only 2 kinds of causative mutations were identified in the population, mostly in the homozygous state: the well‐known c.525delT and the previously described c.87dupT. In the DMD gene, 12 distinctive patterns of deletion were identified, mostly affecting the dystrophin central region. Conclusions: Our data suggest that a simple molecular screen consisting of 2 allele‐specific polymerase chain reactions (PCRs) and a set of 3 multiplex PCRs can diagnose half of the patients who present with progressive muscular dystrophy in the developing nation of Algeria. Muscle Nerve 56 : 129–135, 2017.